login
G.f. satisfies A(x) = (1 + x/A(x)^2)/(1 - x)^3.
1

%I #11 Oct 18 2023 09:58:29

%S 1,4,1,38,-193,1697,-14298,127836,-1175835,11078851,-106354266,

%T 1036575329,-10230191020,102031153812,-1026763493315,10412602349343,

%U -106308046392516,1091783632303656,-11271378486953873,116907289944782853,-1217649336037820058

%N G.f. satisfies A(x) = (1 + x/A(x)^2)/(1 - x)^3.

%F a(n) = (-1)^(n-1) * Sum_{k=0..n} binomial(3*k-1,k) * binomial(3*(2*k-1),n-k)/(3*k-1).

%o (PARI) a(n) = (-1)^(n-1)*sum(k=0, n, binomial(3*k-1, k)*binomial(3*(2*k-1), n-k)/(3*k-1));

%Y Cf. A366364, A363818.

%K sign

%O 0,2

%A _Seiichi Manyama_, Oct 18 2023